Resequencing of the auxiliary GABAB receptor subunit gene KCTD12 in chronic tinnitus - Sand, Philipp G.; Langguth, Berthold; Itzhacki, Jacob; Bauer, Angelika; Geis, Sandra; Cárdenas Conejo Zugey, Elizabeth; Pimentel, Vanessa; Kleinjung, Tobias (Frontiers in Systems Neuroscience, 2012)
Tinnitus is a common and often incapacitating hearing disorder marked by the perception of phantom sounds. Susceptibility factors remain largely unknown but GABAB receptor signalling has long been implicated in the response to treatment and, putatively, in the etiology of the disorder. We hypothesized that variation in KCTD12, the gene encoding an auxiliary subunit of GABAB receptors, could help to predict the risk of developing tinnitus. 95 Caucasian outpatients with a diagnosis of chronic tinnitus were systematically screened for mutations in the KCTD12 open reading frame and the adjacent 3' untranslated region by Sanger sequencing. Allele frequencies were determined for 14 known variants of which three (rs73237446, rs34544607 and rs41287030) were polymorphic. When allele frequencies were compared to data from a large reference population of European ancestry, rs34544607 was associated with tinnitus (p=.04). However, KCTD12 genotype did not predict tinnitus severity (p=.52) and the association with rs34544607 was weakened after screening 50 additional cases (p=.07). Pending replication in a larger cohort, KCTD12 may act as a risk modifier in chronic tinnitus. Issues that are yet to be addressed include the effects of neighbouring variants, e.g. in the KCTD12 gene regulatory region, plus interactions with variants of GABAB1 and GABAB2.